Mapping Local Potential for Community-Based Mangrove Ecotourism Development in the Coastal Area of Banyuasin Regency - Akbar, Dinar Try; Zahana, Yui; Alfitri, Alfitri; Kholek, Abdul (Seminar Nasional Lahan Suboptimal, 2024)
Akbar, D. T., Zahana, Y., Alfitri, A, & Kholek, A. (2024). Mapping local potential for community-based mangrove ecotourism development in the coastal area of Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 164‒175).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coastal communities face socio-economic pressures and mangrove forest degradation, mangrove ecosystems play an important role in maintaining coastal areas and generating income through sustainable ecotourism. The purpose of this research was to identify local potential in Sungsang IV Village that supports the development of community-based Mangrove Ecotourism. The method used was Community-Based Research with a Participatory Action Research (PAR) approach, involving the active participation of 25 representatives of various community elements through group discussions, diagramming, and participatory mapping. The results showed that Sungsang IV Village has great potential for the development of community-based mangrove ecotourism. Potentials such as the natural wealth of mangrove forests and marine resources, interesting local culture, and encouragement from the government and local organizations. The sustainable tourism analysis identified that there are strong tourist attractions, the need to improve supporting amenity, and the urgency of adequate supporting services. Active community involvement and collaboration with other stakeholders are key factors in an integrated ecotourism development strategy. In conclusion, the development of community-based mangrove ecotourism in the coastal area of Sungsang IV Village has the potential to improve the local economy and preserve the mangrove ecosystem, provided that there is effective multi-stakeholder collaboration in the coastal area.